Polycyclic Aromatic Hydrocarbons May Contibute for Prostate Cancer Progression - Freitas, Mariana (2013)
Prostate cancer is the most common form of cancer affecting men in the Western world. Risk factors include ageing, genetics, recurrent inflammation, lifestyle and diet intake, related to an increase of oxidative stress. Prostate cancer risk is also associated with exposure to carcinogen such as polycyclic aromatic hydrocarbons (PAHs), originated from the incomplete combustion of carbon-containing fuels like tobacco, wood, diesel, or charbroiled meat. Although numerous studies have associated the effect of PAHs to tumour development, few investigations have associated its effects to cancer progression. Considering that prostate cancer patients don’t die from localized prostate cancer but from advanced disease, we are interested in investigating whether PAHs may potentially influence prostate cancer progression and how this could be related to an increase in oxidative stress. Likewise we evaluated the effect of PAHs (pyrene, benzo(a) pyrene, chrysene and benzo(k)fluoranthene) on cell growth and in the expression of molecules involved in cancer me- tastization such as the vascular endothelial growth factor (VEGF) and hypoxia inducible factor (HIF) using prostate- derived cell lines from localized adenocarcinoma (HPV10), bone metastasis (PC3) and in non-neoplastic prostate epi- thelium cells. Moreover, we evaluated oxidative stress parameters, assessing reactive oxygen species (ROS) production and reduced glutathione content. Our data clearly demonstrates that PAHs can stimulate cell growth, particularly in lo- calized cancer cells and induce an increase of VEGF and HIF expression. These results are concomitant with an increase of ROS production, suggesting that PAHs exposure may participate in prostate cancer progression, in part, due to an increase of ROS. Therefore this study suggests that PAHs exposure should be avoided to prevent prostate cancer progression.